Cloning and molecular characterization of Dashurin encoded by C20orf116, a PCI-domain containing protein - Neziri, D.; Ilhan, A.; Maj, M.; Majdic, O.; Baumgartner-Parzer, S.; Cohen, G.; Base, W.; Wagner, L. (Biochimica et biophysica acta, 2010)
Characterization of gene products originating from undefined open reading frames and delineation of biological functions has become the task after the human genome has been decoded. We cloned the human C20orf 116 and defined its transcript in liver, kidney and various brain regions by Northern analysis. Antibodies against recombinant protein used for immunofluorescence and immunoblots confirmed its expression in these tissues. With the focus on kidney, its tubular expression and presence in glomerula were shown. A 28 aa long signal peptide predicted by in silico analysis is reflected by visualization of size variants of ∼ 3 kDa difference suggesting a signal peptidase cleavage of the proform. Cell compartment separation confirmed the presence of Dashurin in peroxisomes/mitochondria, microsomes, cytosol and nucleus. This is in line with green fluorescent protein (GFP)-Dashurin fusion protein shuttling between cytosol and nucleus. Luciferase reporter studies revealed a 2–3 fold increase of promoter activities upon over-expression. Bioinformatic analysis identified a PCI-domain at the C-terminus providing protein–protein interaction capabilities. Our present findings suggest the involvement of Dashurin in gene transcription or mRNA translation. Dashurin shares the PCI-domain with three multisubunit protein complexes (26S proteasome, COP9 signalosome and eIF3 translation initiation factor).